Active versus borderline myocarditis: clinicopathological correlates and prognostic implications. Issue 3 (1st March 2002) - Angelini, A; Crosato, M; Boffa, G M; Calabrese, F; Calzolari, V; Chioin, R; Daliento, L; Thiene, G
Abstract : Objective: To compare active (AM) with borderline (BM) myocarditis to verify whether the pathological distinction between the two forms may help to identify patients with different clinical and haemodynamic characteristics and to aid prognosis. Materials: Myocarditis was diagnosed in 56 patients on endomyocardial biopsy (EMB) within one year from clinical onset of the disease between 1991 and 1998. Fourteen patients were excluded because of a lack of adequate and complete information. EMBs and clinical records of the 42 remaining patients were reviewed. Immunohistochemistry on bioptic samples was regularly performed. Polymerase chain reaction (PCR) for a panel of viruses was performed in 23 patients (55%). Clinicopathological correlations were calculated. Results: The histological diagnosis was AM in 26 patients (62%) and BM in 16 (38%). Significant differences were found in the following parameters: presence of left bundle branch block on ECG (AM 2 (8%) v BM 5 (31%), p = 0.05); left ventricular volume on echocardiogram (mean (SD) AM 90 (42) ml/m 2 v BM 128 (50) ml/m 2, p = 0.002); mass to volume ratio (AM 1.0 (0) v BM 0.8 (0.1), p = 0.03); time interval between clinical onset of the disease and EMB (AM 40 (55) v BM 90 (93) days, p = 0.04); and degree of inflammatory infiltrates, scored on a scale of 0 to 3 (AM 1.65 (0.8) v BM 0.85 (0.3), p = 0.004). In 6 of 15 patients (40%) with AM and in 2 of 8 (25%) with BM, a viral genome was detected by PCR (NS). At follow up, no differences in death or heart transplantation were detected between the two forms (AM 4 patients (15%) v BM 2 patients (12.5%)). Three of eight PCR positive patients (37.5%) and 1 of 15 virus negative patients (7%) died or underwent heart transplantation. Conclusions: BM seems to encompass inflammatory forms with a less aggressive inflammatory infiltrate evolving towards left ventricular dilatation. The term "chronic myocarditis" seems to be more appropriate. The absence of myocyte necrosis does not predict a more favourable prognosis, whereas the absence of a viral genome seems to predict it.